THE EFFECT OF COMPETENCE AND CAREER IMPROVEMENT ON PERFORMANCE WITH OCCUPATIONAL HEALTH AND SAFETY AS INTERVENING VARIABLES AT PT PLN (PERSERO) UP3 PEMATANGSIANTAR - Hikmaturriza; Mesra B; Muhammad Isa Indrawan; Kiki Farida Ferine (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to analyze the effect of competence and career enhancement with occupational health and safety as an intervening variable at PT PLN (Persero) UP3 Pematangsiantar. There is no influence of competence on improving employee careers within PT PLN (Persero) UP3 Pematangsiantar and improving employee health and safety. This study uses a quantitative approach with a survey method. The sample amounted to 130 people consisting of 92 employees scattered in the Customer Service Unit (ULP) and 48 people who were in the Customer Service Unit Office (UP3) Pematang siantar. The data analysis technique uses Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results showed that there was one hypothesis that was rejected, namely employee competence and career advancement had a positive but insignificant effect on employee performance and occupational health and safety on career advancement through competency improvement and six more hypotheses were accepted. These findings indicate that improving individual competencies is key in career advancement towards performance with OHS as the main objective. Therefore, it is recommended that organizations continue to encourage competency improvement to improve performance so that employee career advancement is also aligned with competency improvement.